Structural, Photoluminescence and Colorific Properties of Sm3+ doped ZnMoO4 Phosphors for Warm White LEDs - Mallikarjuna, M.; Chengaiah, Thummala; Baby, Y.; Moulika, G.; Raju, Borelli Deva Prasad (Asian Journal of Chemistry, 2026)
Zinc molybdates (ZnMoO4) phosphors activated with different samarium (Sm3+) amounts (0.5, 1.0, 1.5 and 2.0 mol%) were synthesised using a low temperature initiated citrate gel combustion process. The crystal structure of ZnMoO4:Sm3+ phosphors were analysed by XRD and their size was determined to be approximately 20 nm by the Scherrer equation. The FTIR spectral studies confirmed the presence of the distinct functional groups in the prepared phosphors. When the n-UV was excited to 402 nm, four emission maxima (PL) were detected at 567, 602, 649 and 708 nm. These were linked to the Sm3+ ion transitions: 4G5/2→6H5/2 (yellow), 6H7/2 (orange), 6H9/2 (reddish orange) and 6H11/2 (red). Dexter and Shulman’s theory studied the multipolar interaction that causes photoluminescence (PL) quenching via dipole-dipole type interaction in the present ZnMoO4:Sm3+ phosphors. The double-exponential function was used to fit the decay curves of the prepared phosphors and their lifetimes were found to be 1.23, 1.19, 1.11 and 1.09 ms. The colorimetric characteristics, which span the values (x, y) of 0.60 and 0.40, the colour purity of 96% and the colour temperatures below 2000 K, indicate that the fluorescent materials ZnMoO4:Sm3+ have great potential for use in light-emitting diodes (warm-LEDs).